The Effects of Innovative Work Practices on Employee Health and Happiness as Measured by Engagement and Job Satisfaction - Andi Marta; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Examining the mediating roles of Employee Engagement (EE) and Employee Job Satisfaction (EJS), this study seeks to understand how Innovative Work Practices (IWP) affect Employee Health and Happiness (EHH) at PT. Bank XYZ. The researchers used Partial Least Squares (PLS) analysis as part of a quantitative study strategy. Using a 5-point Likert scale, 187 respondents from PT. Bank XYZ Region 02 were surveyed online to gather data on IWP, EHH, EE, and EJS. The research concluded that IWP significantly affects EHH both directly and indirectly via EE and EJS. In order to keep employees healthy, happy, and productive, the results stress the significance of making the workplace accommodating and supportive. Management at PT. Bank XYZ should, therefore, make promotion policies clearer, increase stress management training, and make work location flexibility more robust. Staff morale and output can be boosted and turnover can be decreased by creating a more positive work atmosphere that values and supports employees emotionally. To further enhance Employee Health and Happiness and support the organization's overall goals, it is essential to strengthen IWP practices, such as flexible work arrangements and the use of helpful technological tools.